Genetics of bovine respiratory disease in feedlot cattle - McAllister, Chase, author; Enns, Richard Mark, advisor; Crews, Denny H., 1967-, advisor; Van Campen, Hana, committee member (Colorado State University. Libraries, 2010)
Bovine respiratory disease (BRD) is one of the most prevalent and economically limiting diseases facing the United States beef industry today. Therefore, the objectives of this study were to (1) characterize the occurrence and prevalence of BRD in feedlot steers utilizing three disease classifications; treatment records (Trt), lung lesions present at harvest, and total BRD (treatment or lung lesion or both), (2) to examine the effects of Trt, number of treatments (NumTrt), mean lung score, lesions present, and total BRD on economically relevant carcass traits, and(3) to estimate heritabilities for BRD classifications and associated genetic and environmental correlations with economically relevant carcass traits. Data included health and carcass records on 2,870 crossbred steers managed in a commercial feedlot in Southeast Colorado over a two year period. Disease prevalence varied from 45% (n = 698) to 7% (n = 94) in years one and two, respectively. Averaged across the two year period, 27.6% of the steers exhibited clinical signs and were treated for BRD. Lung lesions were collected on 1,226 and 1,261 steers in year one and year two, respectively. Lesions were present in 71% in of steers year one and 47% in year two, and were present in 59% (n=1,461) of the steers over the two year period. Incidence for total BRD, was 76%, 59%, and 64% for years one, two, and overall, respectively. A subset of data (n = 1,260) of animals with birth information was used to evaluated the effect of age (P > 0.05) and BRD classification on carcass traits. Similarly, two models were fitted to the complete data to test the effect of receiving BW as an approximation for age. Evaluation of the models indicated receiving weight to be a significant fixed effect for prediction of carcass merit (P < 0.001). Incidence of BRD in the feedlot had a negative impact on both marbling score (MS) and subcutaneous backfat thickness (Fat) (P < 0.001), while accounting for minimal variation (P > 0.05) in HCW and LM area after adjusting for fixed contemporary group effects and receiving BW. However, animals that were chronically infected (at least 3 treatments) had reduced HCW (-16.5 ± 4.5 kg) and LM area (4.9 ± 1.25) (P < 0.05) compared to steers that were never treated. Lesions present at harvest did not have a significant effect (P > 0.05) on any evaluated traits. Animals that were categorized as suffering from BRD by the definition of total BRD had reduced MS (6.1 ± 2.8) and Fat (0.39 ± 0.18) (P < 0.05) when compared to healthy steers. Heritability estimates of BRD susceptibility were 0.15 ± 0.06, 0.04 ± 0.03, 0.0 ± 0.0, 0.04 ± 0.06, and 0.07 ± 0.06 for Trt, NumTrt, mean lung score, lesions present, and total BRD, respectively. Genetic correlations were not estimated for mean lung score due to the lack of genetic variability. Genetic correlations of Trt with carcass traits were unfavorable (0.19 ± 0.30) for HCW and LM area (0.03 ± 0.25), and favorable for MS (-0.30 ± 0.21) and Fat (-0.004 ± .26). Genetic correlations for NumTrt were similar at 0.23 ± 0.42, -0.05 ± 0.35, -0.29 ± 0.29, and -0.06 ± 0.35, between HCW, LM area, MS, and Fat, respectively. Estimates of genetic correlations for presence of lesions were zero for all traits. Estimates for total BRD were opposite when compared to Trt, and NumTrt at -0.03 ± 0.4, -0.35 ± 0.36, 0.28 ±0.30, and 0.12 ± 0.35 between HCW, LM area, MS, and Fat, respectively. Results indicate that with selection genetic improvement can be made over time by utilizing feedlot health records. Genetic correlations between treatments records and carcass traits were in general favorable and would increase profitability when incorporated into selection programs.
Department Head: William R. Wailes.
Keywords: Bovine pneumonic pasteurellosis; Cattle -- Diseases -- Genetic aspects; Pasteurella